Analysing the opinions of UK veterinarians on practice-based research using corpus linguistic and mathematical methods - Huntley, Selene J.; Mahlberg, Michaela; Wiegand, Viola; van Gennip, Yves; Yang, Hui; Dean, Rachel S.; Brennan, Marnie L. (Elsevier, 2018)
The use of corpus linguistic techniques and other related mathematical analyses have rarely, if ever, been applied to qualitative data collected from the veterinary field. The aim of this study was to explore the use of a combination of corpus linguistic analyses and mathematical methods to investigate a free-text questionnaire dataset collected from 3796 UK veterinarians on evidence-based veterinary medicine, specifically, attitudes towards practice-based research (PBR) and improving the veterinary knowledge base.